PBA ; General Alfredo Lim ; Bilmoko [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
The controversial issue of game fixing in basketball ; A profile of the fearless general of the Manila Western Police District. A San Miguel beer advertisement stirs a hornet's nest and the song of Fred Panopio that talks about women whose every whim is granted.